Effectiveness of digital resuscitation pad technology innovation on the accuracy of cardiac and lung resuscitation compression - Endiyono, Endiyono; Adhi, M. Hanif Prasetya; Royan, Royan; Taufiq, Arif Johar (Alma Ata University Press, 2024)
Background: Cardiac arrest is a crucial problem because it has a short rescue time and requires optimal assistance competence. The global incidence of cardiac arrest is 50-60 per 100,000 per year, while in Indonesia it is 10,000 per year or 30 incidents every day. This is an important problem that must be addressed immediately, apart from improving skills, by using innovative supporting tools. This tool is still very limited and does not even exist in Indonesia.Objectives: To determine the effectiveness of digital resuscitation pads (petitions) on the accuracy of compression of cardiac and pulmonary resuscitation.Methods: The number of samples in this study was 46 respondents as the case group and as the control group. In the case group, we provided the innovative Digital Resuscitation Pad tool and the rhythm of tapping to perform compressions, while in the control group they were only guided by the rhythm of tapping. The inclusion criteria include respondents who have practiced CPR for lay people appropriately. The instrument uses a questionnaire with a validity test of r table 0.621 and reliability r table 0.539. The analysis uses the Wilcoxon test using total sampling.Results: Based on the researchers' findings in this research, in the control group, 56.52% of respondents performed inappropriate compression, meaning that 26 respondents, more than half of the respondents provided compression that was not of good quality. After being given the Digital Resuscitation Pad, compression quality increased to 86.95% or 29 respondents provided quality compression.Conclusions: There is an influence of the Digital Resuscitation Pad on the accuracy of Cardiac and Pulmonary Resuscitation compressions. Researchers concluded that the Pad Digital Resuscitation device could improve the quality of student compressions over a measurable distance even though BMI indirectly plays an important role in nurses' performance in providing optimal cardiopulmonary resuscitation